7.4 DESIGN FEATURES OF THE JOINTLESS TRACK ON BRIDGES - Makhamajanov Shukhratjon Shavkat ugli, Umaraliev Shahjahan Mukhammadrozi ugli, Tadjibaev Sherzod Amirkulovich, Abdualiev Elyorbek Begali ugli. (Innovative technologies in construction Scientific Journal, 2024)
The article describes the conditions of laying and maintenance of a jointless track on bridges. The main types of bridge webs used and schemes for fixing jointless rail lashes on bridges are described. Keywords: jointless track, rail lashes, bridge, equalizing rail, superstructure. The advantages of a jointless track are primarily in saving labor costs for the maintenance of the railway track and in extending the service life of all elements of the upper structure of the track. With a jointless track, noise and environmental pollution from dusty loads are reduced. Reinforced concrete sleepers are mainly used on the jointless track, which cannot be used on the link track, which makes it possible to save wood [1.2]. Depending on the design, the lengths of the superstructures, the lengths of the temperature spans, the placement schemes of the supporting parts, the construction of the bridge bed, the annual temperature differences of the rails, the jointless track can be laid without breaks or with design breaks of the lashes within the bridge. By design breaks of the lashes is meant the device of a jointless track with equalizing rails, equalizing joints or equalizing devices. The laying of a jointless track on bridges must be carried out in accordance with the project. The project of laying a jointless track without breaking the lashes on all bridges should include [4]: the lengths of the lashes, their layout schemes on the bridge and approaches with reference to the rear walls of the abutments, the construction of fasteners, a sub-rail base; the scheme of fastening lashes on bridges and approaches; the temperature of fastening the lashes; the design of security devices; the project of work on the laying of a jointless track. There are two types of bridge bed used on bridges: ballast (with ballast riding) and ballast-free. The design of the bridge bed must comply with the technical standards and requirements set out in the "Instructions for the design and construction of the bridge bed on railway bridges". A bridge bed with a ballast ride is used with reinforced concrete superstructures up to 33 m long and steel-reinforced concrete ones with a length of more than 33 m [3.4.5.6.7.8.9.10.11]. On reinforced concrete bridges with spans up to 33 m and riding on ballast, a joinless track of the same design as on the roadbed is used. As a rule, rail lashes cover the entire bridge, and their ends are located no closer than 50-100 m from the cabinet walls of the bridge abutments.